Bursal immunopathology and transcriptome analysis of different chicken breeds and lines following infectious bursal disease virus infection - Mohd Isa, Noor Farhanah (2017)
Infectious bursal disease virus (IBDV) infects primarily B cells and macrophages causing the destruction of bursa of Fabricius with varying degree of histopathological lesions depending on the virus virulence. Studies on selected inbred chicken lines and comparison between the layer and meat-type chickens showed different genetic susceptibility towards IBDV infection. However, the immunological mechanisms that associate with the genetic susceptibility towards IBDV have not been thoroughly studied. Therefore, the aim of this study is to perform a genome-wide bursal transcriptome profiling analysis and to characterize the association between the expressions of various immune-related genes with the outcome of very virulent (vv) IBDV infection in different chicken breeds. This study focus on two types of vvIBDV strains, UK661 and UPM0081; with UK661 used in the infection of different inbred lines, meanwhile UPM0081 used in the infection of different chicken breeds. Transcriptome expression profiling of bursa of Fabricius collected at 3 days post-infection (dpi) of six different inbred chickens namely Line 6, 7, 15, N, O and P following infection with UK661 vvIBDV strain have successfully identified 4,588 differentially expressed (DE) genes, with 2,985 genes were up-regulated while 1,642 genes were down-regulated. Genes that were up-regulated are primarily pro-inflammatory cytokines, interferon-related genes, stress protein-related genes such as IFNG, IL6, IL15, IL12B, TLR3, CXCLi2, CCL4, IRF10, NOS2, HSPB1, and other mediators that are associated with macrophage and T lymphocytes activation. Meanwhile, the expressions of IFNB and IFNλ3 (IL28B) were detected only after the infection. Variation in the expression of class I MHC gene was also detected in some of the inbred lines following vvIBDV infection. Meanwhile, genes that associated with B cell functions (BLNK, IGJ and VPREB3) and apoptosis (CASP3 and DFFB) were down-regulated, together with genes involved in p53 signaling. Study on Line P and Line N chickens showed that differential expression of selected immune-related genes may be influenced by the viral copy number (p<0.05), but not histopathological lesions since both lines showed severe bursal lesions (p>0.05). The association of the expression of different immune-related genes with the outcome of IBDV infection was further analyzed in different chicken breeds including the specific-pathogen-free (SPF) chicken, village chicken and jungle fowl following infection with a local vvIBDV isolate UPM0081 at a different dosages. In general, SPF chicken is more susceptible towards UPM0081 infection followed by jungle fowl and village chicken based on clinical signs, mortality, and viral copy number. Regardless of the chicken breeds, chickens infected with high dose of UPM0081 (106.8 EID50) have a higher percentage of macrophages and T cells populations in the bursa of Fabricius compared to chickens infected with low dose of the virus (103.8 EID50). However, reduction of IgM+ cell was highest in jungle fowl from the high dose group after 24 hours of infection suggesting that IgM+ cell of jungle fowl is highly susceptible towards vvIBDV infection. In addition to that, high dose infection stimulated higher and early expression of IFNG, IL6, IL12B, IL28B and CXCLi2. In conclusion, all the inbred and chicken breeds were succumbed towards vvIBDV infection and induced the activation of expression of pro-inflammatory cytokine, chemokines and Th1-associated cytokines. However, SPF chickens were more susceptible towards the infection, compared to other chickens, while Line P that has higher viral copy number induced higher expression of selected immune-related genes. It seems that the differences in the level of host susceptability towards vvIBDV infection are probably due to complex association involving amount of viral copy number, virus infectious dose, variation in the expressions of immune-related genes, severity of bursal lesion and infiltration of immune-cells population in the bursa of Fabricius.